INNOVATIVE APPROACH TO FINANCING EXPORTING COMPANIES - Imamova Nasiba Muzafarovna (KONFERENSIYALAR, 2025)
The national economy development to a qualitatively new level, as well as introduction of innovations requires a radical reconsideration of the role of exporting companies which hold a particular position have a place in the economic development. This thesis describes the financing processes of exporting enterprises